FAVORABLE STRUCTURES FOR HIGHER FULLERENES - COMMENT - Manolopoulos, D (1992)
A corrected version of the ring spiral computer code finds 1812 spectrally distinct fullerene isomers of C60, 22 more isomers than are found by the independent computer enumeration method of Liu, Schmalz and Klein. © 1992.